A CFD study on the reacting flow of partially combusting hot coke oven gas in a bench-scale reformer. (1st November 2015) - Li, Chengyi; Appari, Srinivas; Tanaka, Ryota; Hanao, Kyoko; Lee, Yeonkyung; Kudo, Shinji; Hayashi, Jun-ichiro; Janardhanan, Vinod M.; Watanabe, Hiroaki; Norinaga, Koyo
Highlights: 3D CFD modelling for bench scale hot coke oven gas reforming. Eddy dissipation concept for turbulence–chemistry interaction. Effect of radiation from flame to the thermocouple sheath on temperature measurement. Well reproductions of gas concentration and temperature profiles. Abstract: A computational fluid dynamics (CFD) approach to simulate reacting flow in a hot coke oven gas (HCOG) reformer is presented. The HCOG was reformed by non-catalytic partial oxidation in a tubular reactor (0.6 m i.d. and ∼4.1 m long) with four oxygen nozzles (0.0427 m i.d.), which was installed on a platform of an operating coke oven. The reforming of HCOG, a multi-component mixture, in a turbulent flow was simulated numerically by considering both chemical reactions and fluid dynamics. The detailed chemical kinetic model, originally consisting of more than 2000 elementary reactions with 257 species, was reduced to 410 reactions with 47 species for realising a kinetic model of finite rate reactions with a k – ε turbulence model. The calculation was carried out using the eddy dissipation concept (EDC) coupled with the kinetic model, and accelerated using the in situ adaptive tabulation (ISAT) algorithm. Numerical simulations could reproduce the reformed gas compositions fairly well, such as H2, CO, CO2, and CH4, as well as the temperature profile in a HCOG reformer as measured by thermocouples.